La tele-educación y la evaluación de competencias profesionales de los auxiliares de enfermería en Brasil - Marques, Claudia Maria da Silva; Egry, Emiko Yoshikawa; Silva, Maria Bonifácio; Ribeiro, Maria Cecília; Coelho, Marta Pazos Peralba; Fonseca, Rosa Maria Godoy Serpa da; Morais, Teresa Christina Pereira (Revista da Escola de Enfermagem da USP, 2007)
This paper presents Brazilian's experience with the organization of methods and strategies for the assessment of competencies for technical level of nursing workers. The evaluative process proposed includes the creation of a learning-oriented and distance-based virtual assessment environment. The proposed methodology for professional competencies assessment adopted a critical-emancipatory perspective. A tele-education environment was deployed, involving software development - a virtual man - and an assessment cybertutor. Learning modules for the cybertutor were developed and videos of clinical simulations, structured around assessment in cognitive, behavioral, and simulation areas. The evaluation modules considered aspects of competencies in know-know, know-how and know-act professional ethics. Also the variability of practices of nursing - hospitals and primary health care units - was considered. This instrument showed as an important strategy for the optimization of assessment procedures that are widely used across Brazil and it is a powerful tool for incorporation into the continuing professional education.